"Where to" micromultinationals? A tribute to Professor Pavlos Dimitratos. Issue 4 (August 2021) - Ji, Junzhe; Li, Nicolas; Liouka, Ioanna; Fletcher, Margaret; Tang, Yee Kwan; Slow, Jonathan
Abstract: This reflection serves as a tribute to Professor Pavlos Dimitratos by providing a state-of-the-art understanding of micromultinationals (mMNEs), an important term initially coined by Pavlos and his colleagues (2003) in their European Management Journal article "Micromultinationals: New Types of Firms for the Global Competitive Landscape" to capture the rising phenomenon of international small- and medium-sized enterprises (SMEs) with advanced modes of entry. Whilst underexplored, such firms have critical research, managerial, and policymaking implications for their increasing population and significant value-added activities in home and host economies relative to exporting firms. Based on a short analysis of existing mMNE studies, we appeal for more scholarly attention to their evolution, behavioural characteristics, and consequences, particularly in the area of SME internationalisation. We suggest several promising future directions to investigate this intriguing type of entrepreneurial firms and, using a Scottish context, show how they are appealing to policymakers.